Enhanced detection of ponceau 4r food dye by glassy carbon electrode modified with reduced graphene oxide - de Moraes, Paloma B. [UNESP]; Hudari, Felipe F. [UNESP]; Silva, João P. [UNESP]; Zanoni, Maria V. B. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2018)
This paper reports the development of a glassy carbon electrode modified with a reduced graphene oxide (r-GO/GCE) for the determination of the food dye named Ponceau 4R (PNC). The modified sensor presented excellent signal gain in relation to the GCE and GCE modified with graphene oxide besides exhibiting well defined oxidation peaks for PNC at potential of 0.61 V. Through the application of square wave voltammetry using the medium of 0.1 mol L−1 Britton-Robinson (BR) buffer (pH 5.0), analytical curves were constructed under optimized conditions, where linear regions were found within the range of 0.200 to 20.0 μmol L−1. The limits of detection and quantification were 2.84 × 10−8 and 9.46 × 10−8 mol L−1, respectively. The sensor was successfully applied towards the determination of PNC in instant juice sample. A comparison made between the result obtained through the application of this sensor and via the high-performance liquid chromatography (HPLC) technique showed no significant difference between the two methods.
Keywords: Dye; Electroanalysis; Electrochemical sensor; Voltammetric determination; Voltammetric sensor